2016
DOI: 10.1038/srep36526
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing succinic acid biosynthesis in Escherichia coli by engineering its global transcription factor, catabolite repressor/activator (Cra)

Abstract: This study was initiated to improve E. coli succinate production by engineering the E. coli global transcription factor, Cra (catabolite repressor/activator). Random mutagenesis libraries were generated through error-prone PCR of cra. After re-screening and mutation site integration, the best mutant strain was Tang1541, which provided a final succinate concentration of 79.8 ± 3.1 g/L: i.e., 22.8% greater than that obtained using an empty vector control. The genes and enzymes involved in phosphoenolpyruvate (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Other contaminants, also present in binding assays, could also have influenced previous experiments (Wei et al, ; Zhu et al, ). For instance, counter ions present in phosphorylated metabolite salt solutions introduced along with the ligand might affect electrostatic interactions involved in ligand–protein or protein–DNA contacts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other contaminants, also present in binding assays, could also have influenced previous experiments (Wei et al, ; Zhu et al, ). For instance, counter ions present in phosphorylated metabolite salt solutions introduced along with the ligand might affect electrostatic interactions involved in ligand–protein or protein–DNA contacts.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the significant differences between upper glycolysis in P. putida and E. coli the regulation of Cra in these organisms might be also different. More recently, mutants of Cra were reported to display affinities for FBP from nano to low micromolar range (Wei et al, ; Zhu et al, ). However, these authors could not find a significant effect of these mutations on either the regulation Cra’s DNA‐binding activity in vitro or on transcriptional control of its targets in vivo (Wei et al, ; Zhu et al, ), which casts doubts about the specificity and the functional consequences of the alleged change in Cra’s affinity for FBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the above limitations, researchers have tried to develop various metabolic engineering strategies to enhance SA production mostly in E. coli [4][5][6][7][8]. For example, yield was…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, a higher Cra-FBP affinity ( K d  = 130 ± 37 nM) was obtained, while the K d value of wild-type Cra with FBP was 1400 ± 150 nM. It suggested that the enhanced binding affinity of the Cra mutant for FBP may contribute to succinate biosynthesis [23]. However, research on how changes in effector binding affinity modulate DNA-binding and, therefore, the cell phenotype, is limited.…”
Section: Introductionmentioning
confidence: 99%